( 3 9 3 9 7 8 7 8 ) m o d 7 8 7 9 = ?
Note : You may use the fact that 7879 is prime.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice! I knew Wilson's Theorem was the key, (which is why I just guessed at 7 8 7 8 as the answer), but I didn't know about the refinement, (which finally made sense to me after a few minutes). Thanks for this new bit of knowledge. :)
Log in to reply
I answered − 1 , which is technically correct but not recognized by the website :)
Anyway, here is a more elementary solution: Note that 7 8 7 8 ≡ − 1 , 7 8 7 7 ≡ − 2 , … , 3 9 4 0 ≡ − 3 9 3 9 modulo 7879. Therefore ( 7 8 7 8 3 9 3 9 ) ≡ 3 9 3 9 ⋅ 3 9 3 8 ⋯ 1 3 9 4 0 ⋅ 3 9 4 1 ⋯ 7 8 7 8 ≡ 3 9 3 9 ⋅ 3 9 3 8 ⋯ 1 ( − 3 9 3 9 ) ⋅ ( − 3 9 3 8 ) ⋯ ( − 1 ) ≡ 3939 times ( − 1 ) ⋅ ( − 1 ) ⋯ ( − 1 ) ≡ ( − 1 ) 3 9 3 9 ≡ − 1 . (It is essential that the base of modulo, 7879, is prime. Otherwise we would end up dividing by a zero divisor, which is undefined.)
Did it the same way
Observed features for prime numbers from 3 to 53 and realized. 7878 C 3939 must be an integer!
If not 7878, then it must be 1. Tried with 7878 correct! Calculator cannot tell the answer; it only tells a wrong answer of // 6526.4351304442254481560126764616 //.
For X: Not prime and V: Prime for the following,
...
7875 X
7877 V
7879 V
7881 X
7883 V
7885 X
...
Most likeliness for 7879 Prime is having a remainder of 7878.
Answer: 7878
Problem Loading...
Note Loading...
Set Loading...
Wilson's Theorem does the job. With p = 7 8 7 9 and m = 2 p − 1 = 3 9 3 9 , we know that ( p − 1 ) ! ≡ p − 1 ( m o d p ) and ( m ! ) 2 ≡ ( − 1 ) m + 1 = 1 ( m o d p ) , by a straightforward refinement of Wilson's Theorem. Thus ( 3 9 3 9 7 8 7 8 ) = ( 3 9 3 9 ! ) 2 7 8 7 8 ! ≡ 7 8 7 8 ( m o d 7 8 7 9 )
The refinement of Wilson's Theorem is based on the factorization − 1 ≡ ( p − 1 ) ! = 1 ∗ 2 ∗ . . . ∗ m ∗ ( p − m ) ∗ ( p − ( m − 1 ) ) ∗ . . . ∗ ( p − 1 ) ≡ ( m ! ) 2 ( − 1 ) m ( m o d p )